2013
DOI: 10.1093/infdis/jit651
|View full text |Cite
|
Sign up to set email alerts
|

Correlate of Immune Protection Against HSV-1 Genital Disease in Vaccinated Women

Abstract: The protection against HSV-1 infection observed in the Herpevac Trial for Women was associated with antibodies directed against the vaccine. Clinical Trials Registration NCT00057330.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 9 publications
2
94
0
1
Order By: Relevance
“…However, the frequency of shedding is greater in those with recurrent clinical outbreaks (5). Control of virus shedding has been ascribed to cellular immunity (6), whereas protection correlates well with virus neutralization (7,8). Thus, knowing the neutralizing antibody (Ab) response to infection is important for understanding how vaccination may elicit these protective Abs.…”
mentioning
confidence: 99%
“…However, the frequency of shedding is greater in those with recurrent clinical outbreaks (5). Control of virus shedding has been ascribed to cellular immunity (6), whereas protection correlates well with virus neutralization (7,8). Thus, knowing the neutralizing antibody (Ab) response to infection is important for understanding how vaccination may elicit these protective Abs.…”
mentioning
confidence: 99%
“…Immunization with multiple antigens involved in virus entry failed to improve the protection provided by gD2 alone (31). We base our vaccine approach on the observation that most viral vaccines effective against mucosal infection, such as HSV-2, depend on antibodies for protection (32,33). In addition, the gC2 and gE2 immune evasion molecules that we are targeting are expressed on the virion envelope and at the infected cell surface; therefore, they are accessible to blocking antibodies, while T-cell immune evasion molecules are located within infected cells and are difficult to access.…”
mentioning
confidence: 99%
“…They also showed that deletion of gC or gE from HSV-2 increased its susceptibility to neutralization by gD antibodies and suggested that differential effects of gC and gE in the two HSV serotypes may account for the observed differences in neutralization. Separately, Belshe et al (13) reported that among the gD2 vaccine trial participants, serum antibodies against gD2, but not cell-mediated immunity, correlated with protection against HSV-1 genital disease. Given the documented relevance of gD-specific serum antibodies to virus neutralization and protection from disease, our goal in the current study was to dissect the humoral response to gD2 epitopes elicited by the vaccine.…”
mentioning
confidence: 99%